Pengaruh Keselamatan dan Kesehatan Kerja, Lingkungan Kerja terhadap Produktivitas dengan Kepuasan Kerja sebagai Variabel Intervening pada karyawan Dinas Perdagangan dan Perindustrian (Disdagperin) Kabupaten Pati - Sari, Nur Ika (Universitas Muria Kudus, 2023)
This study aimed to analyze the effect of occupational safety and health, work environment on productivity with job satisfaction as an intervention at the Department of Trade and Industry (Disdagperin) Kab. Pati. The sampling method used purposive sampling with the calculation of the Slovin formula, a sample of 132 respondents was obtained. The data analysis method used in this study is SEM PLS analysis using the SmartPLS statistical test version 3.2.9. The results of the analysis of this study indicate that occupational safety and health directly and the work environment have a positive and significant effect on job satisfaction of employees of Disdagperin Pati. Directly, occupational safety and health, work environment and job satisfaction have a positive and significant impact on the productivity of the Pati Industry Industry and Trade Agency employees. Indirectly, occupational safety and health, work environment has a positive and significant effect on productivity through job satisfaction as an intervening variable.